Performance Evaluation of Medical Device Manufacturers Using a Hybrid Fuzzy MCDM - Lee, Yen-Chun; Chung, Pei-Han; Shyu, Joseph Z. (My University, 2017)
Fuzzy multi-criteria decision making (fuzzy MCDM) methods have developed rapidly and have evolved to accommodate various types of applications. This study aimed to explore a performance evaluation model based on a hybrid fuzzy MCDM approach for Taiwan\'s medical device Manufacturers. The hybrid fuzzy MCDM approach was composed of the fuzzy analytic hierarchy process (fuzzy AHP) method and the technique for order performance by similarity to ideal solution (fuzzy TOPSIS) method, to facilitate industrial practitioners on performance evaluation in a fuzzy environment. The proposed performance evaluation model can also enable government policy makers to better understand the complete evaluation process and provide a more effective decision support tool.
Keywords: Performance Evaluation; Fuzzy MCDM; Fuzzy AHP; Fuzzy TOPSIS; Medical Device Manufacturer